Investigation of the Metaphorical Perceptions of the Parents on the Concept of “Mathematics” - Emine Gözel (International Electronic Journal of Elementary Education, 2018)
The main purpose of this research is to reveal the parents’ perceptions of the concept of “mathematics” through metaphors. This research, which is followed by the qualitative research paradigm, is designed with a phenomenology design. This study is consists of 64 parents whose children are primary school students in a public school in the Central Anatolia region during the spring semester of the 2017-2018 academic year. All the parents who participated in the study were included in the study group on a voluntary basis. The data were gathered with the “Mathematics .......”; because ........ “sentence directed to the parents. The data were analyzed by content analysis technique. According to the aim of the study, the perceptions of parents’ emotions and thoughts evoking the mental concept of their parents were examined. As a result of the research, the metaphors are collected under 13 conceptual categories: “life, game, air-water, road-bridge-key, novel writing, functioning iron, tree, chainring, a remaining song and bee “. Especially “life”, “play” and “air-water” metaphors came to the forefront among the perceptions of the “mathematics” concept of the parents.